2021
DOI: 10.1002/etc.5195
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Biofilms—Sink or Source of Microplastics? A Critical Reflection on Current Knowledge

Abstract: The scientific understanding regarding sources, occurrence, and effects of microplastics in the aquatic environment has advanced rapidly, leaving some meaningful knowledge gaps virtually untouched. One of them is the interactions of microplastics and biofilms, microbial communities ubiquitous in aquatic ecosystems and fundamental for a range of ecosystem level processes. It is evident that biofilms can quickly develop on microplastics' surface and consequently change particle properties and as such its fate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Only plastic particles in the nanosize (NP) in a high concentration (100 nm, 100 mg L −1 ) led to a decrease of chlorophyll a content and the activity of ß-glucosidase and leucine aminopeptidase, and induced oxidative stress (Miao et al, 2019). However, there are no reports on effects of MP on periphyton following long-term exposures, as was highlighted also by a recent review (Kalčíková and Bundschuh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Only plastic particles in the nanosize (NP) in a high concentration (100 nm, 100 mg L −1 ) led to a decrease of chlorophyll a content and the activity of ß-glucosidase and leucine aminopeptidase, and induced oxidative stress (Miao et al, 2019). However, there are no reports on effects of MP on periphyton following long-term exposures, as was highlighted also by a recent review (Kalčíková and Bundschuh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Minerals can also incorporate into the biofilm matrix, leading to increases in volume (Flemming and Wingender 2010 ; He et al 2022 ). Kalčíková and Bundschuh ( 2022 ) suggested that biofilm may reduce the bioavailability of MPs and adsorbed pollutants by increasing their sedimentation rate. Therefore, a change in density and sinking velocity of MPs can have an important influence on the environmental fate and transport, thereby affecting their exposure to organisms.…”
Section: Physicochemical Changes Of Mps Induced By Biofilm Formationmentioning
confidence: 99%
“…Finally, Kalcˇíková and Bundschuh (2022) discusses the potential interactions between biofilms and micro-and nanoplastics. Their review proposes three strategies to improve science and policy on the fate of microplastics: (1) assess the ability of the biofilm to retain microplastics, (2) study the trophic transfer from the substrate-associated biofilms to higher trophic levels, and (3) study the effects of environmental and anthropogenic stressors on the release dynamics of trapped microplastics.…”
Section: Relevant and Realistic Assessments Of Micro-and Nanoplastics...mentioning
confidence: 99%